Emerging Role of the Nucleolar Stress Response in Autophagy - Pfister, Astrid S. (Frontiers in Cellular Neuroscience, 2019)
Autophagy represents a conserved self-digestion program, which allows regulated degradation of cellular material. Autophagy is activated by cellular stress, serum starvation and nutrient deprivation. Several autophagic pathways have been uncovered, which either non-selectively or selectively target the cellular cargo for lysosomal degradation. Autophagy engages the coordinated action of various key regulators involved in the steps of autophagosome formation, cargo targeting and lysosomal fusion. While non-selective (macro)autophagy is required for removal of bulk material or recycling of nutrients, selective autophagy mediates specific targeting of damaged organelles or protein aggregates. By proper action of the autophagic machinery, cellular homeostasis is maintained. In contrast, failure of this fundamental process is accompanied by severe pathophysiological conditions. Hallmarks of neuropathological disorders are for instance accumulated, mis-folded protein aggregates and damaged mitochondria. The nucleolus has been recognized as central hub in the cellular stress response. It represents a sub-nuclear organelle essential for ribosome biogenesis and also functions as stress sensor by mediating cell cycle arrest or apoptosis. Thus, proper nucleolar function is mandatory for cell growth and survival. Here, we highlight the emerging role of nucleolar factors in the regulation of autophagy. Moreover, we discuss the nucleolar stress response as a novel signaling pathway in the context of autophagy, health and disease.